Perlindungan Hukum Tenaga Kerja Terhadap Pekerja Yang Terkena Phk di Masa Pandemi Covid-19 di Karawang - Anissa Rizky Salsabila; Imam Budi Santoso; Rohendra Fathammubina (Jurnal Ilmiah Wahana Pendidikan, 2022)
Research on the legal protection of labor for workers who were laid off during the Covid-19 Pandemic in Karawang aims to find out the legal protection from the government for workers, fulfill the rights of workers/laborers and the settlement mechanism in fulfilling the rights of workers affected by layoffs in Karawang. the future of the covid-19 pandemic in Karawang. The problem approach in this study uses a normative juridical approach with descriptive analysis methods. The result of this study is that the legal protection of labor in the era of the covid-19 pandemic, has not been maximized because there are very few rules that emphasize that workers/laborers cannot be arbitrarily fired or get unilateral termination of employment due to the covid-19 pandemic which then results in the existence of unilateral termination of employees in Karawang Regency and the ineffectiveness of the mechanisms that can be carried out if workers/laborers experience problems with employers/companies either bipartite, tripartite or the Industrial Relations Court